Effects of monocolonization with Escherichia coli strains O6K13 and Nissle 1917 on the development of experimentally induced acute and chronic intestinal inflammation in germ-free immunocompetent and immunodeficient mice - Hudcovic, T; Stepánková, R; Kozákova, H; Hrncír, T; Tlaskalová-Hogenová, H (Folia microbiologica, 2007)
Germ-free immunocompetent (BALB/c) and immunodeficient (SCID) mice were colonized either by E. coli O6K13 or by E. coli strain Nissle 1917 and intestinal inflammation was induced by administering 2.5% dextran sulfate sodium (DSS) in drinking water. Controls were germ-free mice which demonstrated only mild inflammatory changes after induction of an acute intestinal inflammation with DSS as compared with conventional mice in which acute colitis of the colon mucosa similar to human ulcerative colitis is elicited. In mice monocolonized with the nonpathogenic E. coli Nissle 1917 the inflammatory disease did not develop (damage grade 0) while animals monocolonized with uropathogenic E. coli O6K13 exhibited inflammatory changes similar to those elicited in conventionally reared mice (damage grade 3). In the chronic inflammation model, immunocompetent BALB/c mice monocolonized with E. coli Nissle 1917 showed no conspicuous inflammatory changes of the colon mucosa whereas those monocolonized with E. coli O6K13 developed colon inflammation associated with marked infiltration of inflammatory cells. In contrast to germ-free immunodeficient SCID mice that died after application of DSS, the colon mucosa of SCID mice monoassociated with E. coli Nissle 1917 exhibited only moderate inflammatory changes which were less pronounced than changes of colon mucosa of SCID mice monoassociated with E. coli O6K13.
Keywords: gnotobiologické modely; Inflammation; infekce vyvolané Escherichia coli; Mice, SCID; Germ-Free Life; Colitis; myši inbrední BALB C; Escherichia coli Infections; střevní sliznice; Gastrointestinal Tract; Escherichia coli; Mice, Inbred BALB C; zánět; Animals; Dextran Sulfate; zvířata; myši SCID; Intestinal Mucosa; gastrointestinální trakt; myši; kolitida; Mice; síran dextranu